Long-term effects following 4 years of randomized treatment with atorvastatin in patients with type 2 diabetes mellitus on hemodialysis - Krane, Vera; März, Winfried (Kidney international, 2016)
The 4D (Die Deutsche Diabetes Dialyse) Study was a randomized, double-blind trial comparing 4 years of treatment with atorvastatin to placebo in 1255 hemodialysis patients with type 2 diabetes. The primary end point of cardiovascular events (cardiac death, myocardial infarction, and stroke) was non-significantly reduced by 8%. However, long-term effects remained uncertain. Therefore, surviving patients were invited to a follow-up survey done by questionnaire. Post-trial statin therapy was at nephrologist discretion, and outcomes were centrally adjudicated and analyzed by intention to treat and time to first event in the original treatment groups. Median overall follow-up was 11.5 years. Post-trial statin use and low-density lipoprotein cholesterol levels did not differ between groups. Statin treatment non-significantly affected the former primary outcome (relative risk, 0.91; 95% confidence interval, 0.78-1.07). The risk of all cardiac events combined and the risk of cardiac death were significantly lower in the original statin group compared to placebo (0.83, 0.70-0.97, and 0.80, 0.66-0.97). No significant effect was detected on cerebrovascular events, fatal stroke, fatal cancer, non-vascular, or all-cause death. No rhabdomyolysis was reported. Thus, after 4 years of atorvastatin treatment in diabetic hemodialysis patients, similar effects on outcomes were found after 11.5 years of follow-up as were found at the end of the original study. There was no evidence of emerging hazards in the long term, confirming current clinical practice guidelines.
Gesehen am 24.06.2019